An Integrated Assessment of Water Quality in Artificial Lakes: A Case Study of Tasik Kemajuan Using Bioindicators, Water Quality Index, and Trophic Status Index - Nurul Syafiqah Abdul Rahman; Siti Hidayah Abu Talib (Journal of Advancement in Environmental Solution and Resource Recovery, 2026)
Artificial lakes play a vital role in water resource management, supporting ecological balance and providing opportunities for recreation, agriculture, and urban water supplies. However, these lakes are increasingly threatened by pollution and eutrophication due to human activities and rapid urbanization resulting in significant ecological challenges. This study investigates the water quality of Tasik Kemajuan, an artificial lake at Universiti Tun Hussein Onn Malaysia (UTHM), by employing a comprehensive approach integrating bioindicators, the Water Quality Index (WQI), and the Trophic Status Index (TSI). The study obtained bioindicator analysis focusing on macroinvertebrates resulting on water quality status of Class II (rather clean to clean) with moderate diversity and favourable ecological conditions. The WQI results averaged between 72.87 and 73.95, classifying the water as slightly polluted (Class III) and emphasizing the need for significant treatment before use. Other than that, TSI scores ranging from 76.36 to 79.51 identified the lake as eutrophic, characterized by nutrient enrichment that leads to excessive algae growth and oxygen depletion. The findings highlight the lake's ecological challenges, particularly nutrient-induced eutrophication, while the integration of these assessment methods provided a holistic understanding of the lake's water quality. Comparative analysis of WQI, TSI, and bioindicator data demonstrated the complementary strengths of these methods, highlighting the need for an integrated approach to water quality assessment. This study underscores the need for targeted management strategies to improve water quality and maintain ecological balance in artificial lakes.